Community Pharmacist Provision of Non-Dispensing Services in Health Professional Shortage Areas - Haley Kessinger; Emily Landis; Natalie DiPietro Mager; Karen Kier (University of Minnesota Libraries Publishing, 2022)
Individuals living in primary care health professional shortage areas (HPSAs) experience health inequities. Community pharmacists are healthcare professionals with an opportunity to provide care to underserved populations. The objective of this study was to compare non-dispensing services provided by Ohio community pharmacists in HPSAs and non-HPSAs. Methods: An electronic, IRB-approved 19-item survey was sent to all Ohio community pharmacists practicing in full-county HPSAs and a random sample practicing in other counties (n=324). Questions assessed current provision of non-dispensing services as well as interest and barriers regarding such services. Results: Seventy-four usable responses were received (23% response rate). Respondents in non-HPSAs were more likely to recognize their county's HPSA status than those in an HPSA (p=0.008). Pharmacies in non-HPSAs were significantly more likely to offer 11 or more non-dispensing services than those in HPSAs (p=0.002). Nearly 60% of respondents in non-HPSAs reported starting a new non-dispensing service during the COVID-19 pandemic compared to 27% of respondents in full HPSA counties (p=0.009). Most commonly reported barriers to providing non-dispensing services in both county types included lack of reimbursement (83%), workflow (82%), and space (70%). Respondents expressed interest in learning more information about public health and collaborative practice agreements. Conclusion: While the need for non-dispensing services is great in HPSAs, community pharmacies in full-county HPSAs in Ohio were less likely to provide these services or begin novel services. Barriers must be addressed so that community pharmacists can provide more non-dispensing services in HPSAs to increase access to care and promote health equity.